African postfoundational practical theology - Müller, J.C. (Acta theologica, 2017)
Practical Theology is located in a fragile, vulnerable space between various disciplines, where it is exposed to multiple different narratives. The author proposes a postfoundational, narrative approach to Practical Theology that favours the local over the global and the specific over generalisations. Africa is taken as the defining context for the understanding and development of a specific postfoundational Practical Theology. People and their stories are central, and this requires a coconstruction of meaning with “co-researchers”. The author’s “Seven Movements”, as published in other articles, is used with an Ubuntu research project as a case study. The “Seven Movements” facilitate the telling and retelling of unheard stories, particularly stories of the marginalised and vulnerable. This way of doing Practical Theology takes the experiences of “co-researchers” seriously and conducts research wíth people rather than on them. The researcher’s focus is concrete, local, and contextual, but also extends beyond the local by engaging in transdisciplinary conversation and developing interpretations that point beyond the local.